Towards tool support for analyzing legacy systems in technical domains - Klammer, Claus; Pichler, Josef (2014 Software Evolution Week - IEEE Conference on Software Maintenance, Reengineering, and Reverse Engineering (CSMR-WCRE), 2014)
Software in technical domains contains extensive and complex computations in a highly-optimized and unstructured way. Such software systems developed and maintained over years are prone to become legacy code based on old technology and without accurate documentation. We have conducted several industrial projects to reengineer and re-document legacy systems in electrical engineering and steel making domains by means of self-provided techniques and tools. Based on this experience, we derived requirements for a toolkit to analyze legacy code in technical domains and developed a corresponding toolkit including feature location and static analysis on a multi-language level. We have applied our approach and toolkit for software systems implemented in the C++, Fortran, and PL/SQL programming languages and illustrate main benefits of our approach from these experiences.